Part 5: Organisational changes required by the reform of the CASA-Sevilla study abroad programme. Issue 3 (1st December 2019) - Infante Mora, Eva; Markot, Marina; Capobianco, Stephen; Ivanchikova, Melina; Kiely, Richard; Feldman, Richard; Cheatle, Amy
Abstract : The action research process initiated in 2015 to make a thorough reform of the CASA-Sevilla study-abroad programme not only produced significant pedagogical developments but also brought about a profound change in the way of working and relating within the programme work organisation itself and with Cornell University colleagues. This section focuses on organisational changes in each of the units involved, and reflects a path full of transitions, diplomacy, exchange of perspectives and inter-institutional as well as intercultural learning. To make these pedagogical reforms work in practice required significant organisational change and support efforts on the part of both CASA-Sevilla and the supporting organisations at Cornell University.